Pengaruh Undang-Undang Keistimewaan Jogyakarta Terhadap Kesejahteraan Masyarakat Daerah Istimewa Yogyakarta - Jawahir Thontowi (UIR Law Review, 2019)
This study intends to analyze the relationship between Law Number 13 of 2012 concerning the Privileges of Jogyakarta to the conditions of social and economic welfare of the Jogyakartan communities. The problem that will be analyzed is why does Act Number 13 of 2012 not yet function effectively in improving the welfare of the Jogyakartan communities. This study uses the socio-legal method. The results of this study indicate that even though the existence of Law Number 13 of 2012 received a positive response from the Jogkartan communities, it has also been implemented in a number of Jogjakarta Special Regional Regulations such as the appointment of public offices, civil service and cultural civilization, but in its failed to improve the Jogyakartan communities welfare because of the availability of factors in the local representative people considering the conflict of interest between members of the Palace families.